2000
DOI: 10.1089/152045500436104
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of an Endangered Species (Bos gaurus) Using Interspecies Nuclear Transfer

Abstract: Approximately 100 species become extinct a day. Despite increasing interest in using cloning to rescue endangered species, successful interspecies nuclear transfer has not been previously described, and only a few reports of in vitro embryo formation exist. Here we show that interspecies nuclear transfer can be used to clone an endangered species with normal karyotypic and phenotypic development through implantation and the late stages of fetal growth. Somatic cells from a gaur bull (Bos gaurus), a large wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
207
2
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(223 citation statements)
references
References 33 publications
10
207
2
4
Order By: Relevance
“…Using antibodies against 5-methyl cytosine, two independent studies showed that the cloned bovine embryos did not undergo normal global demethylation in early embryogenesis and even showed precocious de novo methylation , with a Since the generation of "Dolly," a wide range of mammals have been used for nuclear transfer (NT) and produced live born clones. Interspecies NT (Bos gaurus donor nuclei into domestic cow oocytes) was used to demonstrate the potential to rescue endangered species (only late-stage pregnancies were demonstrated in this report [Lanza et al, 2000b]). a Cultured donor cells were in most cases synchronized (G0/G1) either by serum starvation or contact inhibition before nuclear transfer (NT).…”
Section: Dna Methylation and Ntmentioning
confidence: 99%
See 1 more Smart Citation
“…Using antibodies against 5-methyl cytosine, two independent studies showed that the cloned bovine embryos did not undergo normal global demethylation in early embryogenesis and even showed precocious de novo methylation , with a Since the generation of "Dolly," a wide range of mammals have been used for nuclear transfer (NT) and produced live born clones. Interspecies NT (Bos gaurus donor nuclei into domestic cow oocytes) was used to demonstrate the potential to rescue endangered species (only late-stage pregnancies were demonstrated in this report [Lanza et al, 2000b]). a Cultured donor cells were in most cases synchronized (G0/G1) either by serum starvation or contact inhibition before nuclear transfer (NT).…”
Section: Dna Methylation and Ntmentioning
confidence: 99%
“…This approach was successfully used to produce transgenic sheep, pigs, and cows (reviewed in Campbell et al, 2005). Furthermore, the possibility to rescue endangered species (Bos gaurus) by interspecies NT using domestic animals as oocyte donors has been reported indicating another potentially useful application of NT (Lanza et al, 2000b). It should be emphasized that the abnormalities of cloned animals are likely not problematic for propagating livestock animals, because epigenetic abnormalities are lost in the offspring of the clones (Tamashiro et al, 2002;Jaenisch, 2004).…”
Section: Reproductive Cloningmentioning
confidence: 99%
“…Une autre perspective s'apparente plutôt au clonage interspé-cifique et consisterait à introduire un noyau somatique humain dans un ovocyte de femelle animale, en espérant réaliser un ovule chimérique à l'issue de la méiose in vitro. Ce bricolage a été réalisé avec succès, dans le cadre de la préservation d'animaux menacés, pour des espèces très proches: croisements mouflon/mouton [23] ou bovin sauvage (Bos javanicus)/bovin domestique (Bos taurus) [24]. Des auteurs chinois ont même tenté de conserver ainsi le panda géant, mais leur expérience audacieuse (génome de panda introduit dans l'ovule de lapin et gestation de l'embryon chimérique assurée par une chatte…) n'a pas conduit à la naissance, bien que le dévelop-pement post-implantatoire, chez la chatte, de clones interspé-cifiques panda-lapin soit rapporté [25].…”
Section: Autres Sources D'ovulesunclassified
“…A somatic cell bank consists of ear-tag tissues, which can be preserved in liquid nitrogen (LN) and subsequently used as donor cells for animal cloning. During the last decade, the technique of reproductive somatic nuclear transfer (NT) was successfully applied in livestock (sheep, cattle, goats, pigs, horses), rodents (mice, rats) and pet animals (cats, dogs), as reviewed in Kues and Niemann (2004), and also in the preservation of endangered breeds (Lanza et al, 2000;Wells et al, 1998;White et al, 1999) and wild animal species (Loi et al, 2001). The best success rates in terms of live offspring so far were obtained with cloned cattle and goats.…”
Section: Introductionmentioning
confidence: 99%